(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper investigates how project-based learning (PBL) can be utilized in extracurricular programs within high school foreign language classes. PBL has been found to encourage active and meaningful language use, enhance critical thinking skills, and promote learner independence. The article outlines the benefits, challenges, and methods of implementing PBL and provides actionable strategies for incorporating it into language education.